Settling at Keswick: Affective Bioregionalism in Southey Country - Taylor, Joanna (Romanticism on the Net, 2017)
This article explores how Keswick, a market town in the northern Lake District, became the locus for Southey’s development of his own poetic landscape. In particular, it argues that Southey’s representations of Keswick—the most significant tourist destination in the Romantic-era Lake District—counterpointed the development in the south Lakes of Wordsworthshire, the area around Grasmere and Ambleside that Wordsworth was explicitly claiming as his poetic ground. But, this article suggests, whereas the cultural-geographical legacies of Wordsworthshire were based on texts that advocated what Keats termed the “egotistical sublime,” Southey Country prioritised social interaction. This article explores how Southey’s Lake District was based on texts that emphasised bonds between family and friends that were firmly tied to key locations, particularly his home at Greta Hall and the waterfall at Lodore. In doing so, this article posits a new reading of Lakeland Romanticism that situates this Lake Poet at the centre of a trans-historical community.